Principle of proportionality of punishment in dismissal without just cause and excuse - Ali Mohamed, Ashgar Ali (LexisNexis Malaysia Sdn Bhd, 2014)
The principle of proportionality of punishment implies that the punishment to be imposed on the offender should fit the crime ie the punishment must be proportionate to the severity of the wrong committed. In cases that established misconduct, the disciplinary authority has the discretion to determine the severity of the disciplinary measure justified by the employee’s misconduct. The question remains whether the preferred sanction was warranted in the circumstances, or whether it was proportionate to the gravity of the wrong committed.Hence, this article discusses the application of the principles of proportionality of punishment in dismissal from employment cases. Industrial Court